URGENSI PEMBENTUKAN UNDANG-UNDANG HAK ANGKET DPR RI (THE URGENCY OF MAKING THE LAW ON THE RIGHT OF INQUIRY OF THE HOUSE OF REPRESENTATIVES OF THE REPUBLIC OF INDONESIA) - Novianto Murthi Hantoro (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2017)
Prior to the decision of the Constitutional Court (MK), the implementation of the right to inquiry was regulated in two laws, namely Law No. 6 of 1954 on the Establishment of the Rights of Inquiry of the House of Representatives (DPR) and Law No. 27 of 2009 on MPR, DPR, DPD, and DPRD. Through proposal for judicial review, MK decided the Law on the Rights of Inquiry was null and void because it was not in accordance with the presidential system adopted in the 1945 Constitution. Today, the exercise of the right of inquiry is only based on Law on MPR, DPR, DPD, and DPRD. Nonetheless, the Amendment of Law No. 27 of 2009 into Law No. 17 of 2014 could not accommodate some substances of the null and void Law on the Rights of Inquiry. The urgency of the formulation of the law on the right to inquiry, other than to carry out the Constitutional Court’s decision; are to close the justice gap of the current regulation; to avoid multi-interpretation of the norm, for example on the subject and object of the right of inquiry; and to execute the mandate of Article 20A paragraph (4) of the 1945 Constitution. The regulation on the right to inquiry shall be formulated separately from the Law on MPR, DPR, DPD and DPRD, with at least several substances to be discussed, namely: definition, mechanisms, and procedure, as well as examination of witnesses, expert, and documents. AbstrakSebelum adanya putusan Mahkamah Konstitusi (MK), pelaksanaan hak angket diatur dalam dua undang-undang, yaitu Undang-Undang Nomor 6 Tahun 1954 tentang Penetapan Hak Angket DPR (UU Angket) dan Undang-Undang Nomor 27 Tahun 2009 tentang Majelis Permusyawaratan Rakyat, Dewan Perwakilan Rakyat, Dewan Perwakilan Daerah, dan Dewan Perwakilan Rakyat Daerah (UU MPR, DPR, DPD, dan DPRD). Melalui permohonan pengujian undang-undang, MK membatalkan keberlakuan UU Angket karena sudah tidak sesuai dengan sistem presidensial yang dianut dalam UUD 1945. Pelaksanaan hak angket saat ini hanya berdasarkan UU MPR, DPR, DPD, dan DPRD. Penggantian UU No. 27 Tahun 2009 menjadi UU No. 17 Tahun 2014 tentang MPR, DPR, DPD, dan DPRD ternyata tidak mengakomodasi beberapa substansi UU Angket yang telah dibatalkan. Berdasarkan hal tersebut, terdapat urgensi untuk membentuk Undang-Undang tentang Hak Angket DPR RI. Urgensi tersebut, selain sebagai tindak lanjut putusan MK, juga untuk menutup celah kekosongan hukum pada pengaturan saat ini dan untuk menghindari multi-interpretasi norma, misalnya terhadap subjek dan objek hak angket. Pengaturan mengenai hak angket perlu diatur di dalam undang-undang yang terpisah dari UU MPR, DPR, DPD, dan DPRD, dengan materi muatan yang berisi tentang pengertian-pengertian, mekanisme, dan hukum acara. Pembentukan Undang-Undang tentang Hak Angket diperlukan guna memenuhi amanat Pasal 20A ayat (4) UUD 1945.